(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Stroke, the second leading cause of death worldwide is a multifactorial disease. Several risk factors had been identified for stroke. Hyperhomocysteinemia is one of the latest additions among the risk factors responsible for ischaemic stroke. Though vitamin B12 is one of the causative factors of hyperhomocyteinemia, very few studies showed a relation between ischaemic stroke and Vitamin B12 deficiency. So, this study aimed to find out the association between vitamin B12 deficiency and acute ischaemic stroke. Methods: This case-control study was conducted at the department of Neurology, Mymensingh Medical College & Hospital. Fifty patients of first ever acute ischemic stroke and 50 apparently healthy controls, matched for age (56.90±9.88 versus 52.88±6.18) and sex (31 male and 19 female) were recruited. Vitamin B12 was measured by Enzyme-linked immunosorbent assay and its status was considered as low, borderline and normal with vitamin B12 levels of <180, 180-200 and 200-800 pg/ml, respectively. Results: Mean (±SD) concentration of vitamin B12 in stroke cases and control were 223.84 (±71.764) pg/ml and 306 (±115.40) pg/ml respectively (p=<0.001). Low and borderline vitamin B12 was observed in 22% and 58%of ischaemic stroke patients and 12% and 30%of the healthy controls. Participants with borderline Vitamin B12 plasma level had significantly higher odds of being in the cases compared to participants with normal vitamin B 12 plasma level (OR: 5.61; 95% CI:2.16-14.52, p=<0.001). Similarly participants with low plasma level of vitamin B12 were 5.32 times more likely to be in ischaemic stroke group compared to participants with normal plasma vitamin B12 level (OR: 5.32; 95% CI:1.56-18.14, p=0.008). Conclusion: The study concluded that low serum vitamin B12 level was associated with acute ischaemic stroke.